2007
DOI: 10.1249/mss.0b013e31812e52b3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Uptake Efficiency Slope as a Determinant of Fitness in Overweight Adolescents

Abstract: OUES differs significantly in overweight and nonoverweight adolescents. The wide interindividual variation and the exercise intensity dependence of OUES preclude its use in clinical practice as a predictor of VO2peak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 30 publications
10
65
1
4
Order By: Relevance
“…An example of the OUES is shown in Figure 2, where the graph on the left is not log transformed and is modeled by a logarithmic relationship and the graph on the right is log transformed to reveal a simplified modeled linear relationship, where the slope of the line given is the OUES. found that 24% of severely overweight and 10% of nonoverweight subjects failed to achieve the VO 2peak criteria set forth in the study, representing a lack of potential data if one were to employ maximal exercise measurements only (32).…”
Section: Ouesmentioning
confidence: 98%
See 3 more Smart Citations
“…An example of the OUES is shown in Figure 2, where the graph on the left is not log transformed and is modeled by a logarithmic relationship and the graph on the right is log transformed to reveal a simplified modeled linear relationship, where the slope of the line given is the OUES. found that 24% of severely overweight and 10% of nonoverweight subjects failed to achieve the VO 2peak criteria set forth in the study, representing a lack of potential data if one were to employ maximal exercise measurements only (32).…”
Section: Ouesmentioning
confidence: 98%
“…This allows for fitness and functional comparisons across different subject populations. Recent studies have shown that OUES is influenced by age, body size, and even the musculature of the secondary respiratory muscles (5,32,53,72). Additionally, the two variables comprising the OUES are known to be affected by metabolism; so it is possible that the OUES might vary by maturation as a function of muscle metabolism (14).…”
Section: Significance Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been used to evaluate aerobic fitness in a wide number of subjects, including healthy men [12], overweight adolescents [15], and cardiovascular disease patients [12]. It is interesting to note that the OUES determination is not influenced by some intervenient factors, such as the use of experienced and nonexperienced evaluators or test protocol [12].…”
Section: Introductionmentioning
confidence: 99%